Analysis of dancer in the choreography of the Lilin Siwa dance group in Palembang, South Sumatra - Rully Rochayati; Muhammad Jazuli; Hartono; Wahyu Lestari (Cogent Arts & Humanities)
The polemic for Palembang artists is about dancers. Physically, the established size standards give rise to discrimination for some groups in society. This research emerged because the Lilin Siwa dance does not consider physical size standards, but emphasizes that good dancers can perform dance techniques proportionally. The role of dancers in group choreography is very important, especially in the Lilin Siwa Dance. However, the dancer aspect is often overlooked, even though certain skills are needed that are more than just a performance. The purpose of the research is to examine the specific aspects of dancers in group choreography in the Lilin Siwa Dance. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The analysis identified aspects of the number of dancers, gender and body posture, unity of composition in the group, determination of direction position, distance between dancers, and the presence of the main dancer. Until now, the Lilin Siwa Dance is still preserved by the local community and formal education environment. The research contributes to offering insight into the dancer aspect in dance performances. Increasing awareness of knowledge and mastery of dancer factors for the effectiveness of the Lilin Siwa Dance performance.